2013
DOI: 10.1111/jnc.12470
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine induces dendritic spine remodeling in cultured hippocampal neurons

Abstract: Cholinergic neurons in the CNS are involved in synaptic plasticity and cognition. Both muscarinic and nicotinic acetylcholine receptors (nAChRs) influence plasticity and cognitive function. The mechanism underlying nAChR-induced plasticity, however, has remained elusive. Here, we demonstrate morphological changes in dendritic spines following activation of a4b2* nAChRs, which are expressed on glutamatergic presynaptic termini of cultured hippocampal neurons. Exposure of the neurons to nicotine resulted in a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…Moreover, amplitude of glutamate release induced by nicotine or α4β2 nAChRs agonists has been revealed to be decreased in β2 nAChRs knockout animal model (Lambe et al, 2003, Parikh et al, 2010). A study was performed to determine the morphological effects of nicotine on dendritic spines of α4β2 nAChRs showed that nicotine-induced lateral enlargement in the spine heads of α4β2 nAChRs can lead to glutamatergic synaptic plasticity, since glutamate receptors antagonists blocked the nicotine-induced spine remolding effect (Oda et al, 2014). It is important to note that α4β2 nAChRs antagonist also abolished this effect, which suggests the potential role of this receptor in glutamate release.…”
Section: Role Of Nicotinic Acetylcholine Receptors In the Modulatimentioning
confidence: 99%
“…Moreover, amplitude of glutamate release induced by nicotine or α4β2 nAChRs agonists has been revealed to be decreased in β2 nAChRs knockout animal model (Lambe et al, 2003, Parikh et al, 2010). A study was performed to determine the morphological effects of nicotine on dendritic spines of α4β2 nAChRs showed that nicotine-induced lateral enlargement in the spine heads of α4β2 nAChRs can lead to glutamatergic synaptic plasticity, since glutamate receptors antagonists blocked the nicotine-induced spine remolding effect (Oda et al, 2014). It is important to note that α4β2 nAChRs antagonist also abolished this effect, which suggests the potential role of this receptor in glutamate release.…”
Section: Role Of Nicotinic Acetylcholine Receptors In the Modulatimentioning
confidence: 99%
“…Different combinations of subunits define nAChR subtypes and confer distinguishing biophysical and pharmacological characteristics to the receptor. The a4b2 nAChRs are the predominant heteromeric nAChRs in the mammalian brain (Whiting and Lindstrom, 1987;Flores et al, 1992;Mao et al, 2008) and are thought to mediate important physiologic actions of acetylcholine (ACh) and pharmacological effects of nicotine related to attention and cognition (Picciotto et al, 1995;Guillem et al, 2011;Lozada et al, 2012;Paolone et al, 2013;Oda et al, 2014) and affective states (Mineur and Picciotto, 2010;Turner et al, 2010;Brunzell, 2012, 2015;Hussmann et al, 2014). In addition to their roles in normal central nervous system physiology, considerable evidence points to the involvement of these receptors in nicotine addiction and dependence (Marks et al, 1983;Schwartz and Kellar, 1983;Benwell et al, 1988;Flores et al, 1992Flores et al, , 1997Perry et al, 1999;Staley et al, 2006;Wüllner et al, 2008;Marks et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…; Oda et al . ). Even more surprisingly choline proves to be a potent direct regulator via both muscarinic and nicotinic AChRs of patterned activity within hippocampal networks (Fischer et al .…”
Section: Cholinergic Transmission Signalling and Pathobiologymentioning
confidence: 97%
“…Positive allosteric modulation of the a7-nicotinic AChR is thus attracting appreciable attention so it is interesting to see a note of caution voiced recently about the potential for neuronal injury from overload of intracellular Ca 2+ after dys-regulation of endoplasmic reticulum Ca 2+ (Guerra-Alvarez et al 2015). Other possible targets here include a4-nicotinic AChRs which play a role in remodelling of spine architecture underpinning the cholinergic tuning of brain function and in associated hippocampal synaptic development and plasticity (Nordman et al 2014;Oda et al 2014). Even more surprisingly choline proves to be a potent direct regulator via both muscarinic and nicotinic AChRs of patterned activity within hippocampal networks (Fischer et al 2014) and even more complexity is revealed by new findings that APP interacts with choline transport and its trafficking is sensitive to APP genetic mutants (Cuddy et al 2015).…”
Section: Cholinergic Transmission Signalling and Pathobiologymentioning
confidence: 99%